Rapunzel Syndrome and Small Bowel Intussusceptions Due to a Cotton Thread Bezoar: A Case Report - Vineetha Raghu; Anita N. Nagadi; Ashwini Chethan Kumar (Thieme Medical and Scientific Publishers Pvt. Ltd., 2018)
Rapunzel syndrome is a rare disease in which a trichobezoar extends into the duodenum or distal small intestine. It is associated with compulsive eating of indigestible substances or pica and is more common in cases of underlying psychiatric disturbances. If left untreated, gastrointestinal bezoars with or without the Rapunzel syndrome may lead to several complications such as ulceration, perforation, peritonitis, pancreatitis, biliary obstruction, severe nutritional disturbances, and rarely intestinal obstruction. We present an exceptionally rare case of Rapunzel syndrome caused by a large cotton thread bezoar in an adolescent girl, associated with multiple jejunal intussusceptions. Further, we present a literature review of this entity. An interesting association of bezoar with intussusception is explained. Since a history of pica may not be forthcoming in all cases, it is important to be familiar with the imaging characteristics, complications, and management of bezoars.